Amelogenesis imperfecta: a sign of kidney disorders? (Revista Nacional de Odontología, 2021)
Introduction: Amelogenesis Imperfecta (AI) constitutes a heterogeneous group of alterations, that impact the structure of tooth enamel of genetic origin. This pathology product of physiological changes during odontogenesis modifies the structure and clinical appearance of the enamel, giving it a thin appearance and less resistance. It has been described that AI may appear in isolation or in a syndromic manner.Purpose: Describe the syndromes that impact the renal system and present with amelogenesis imperfecta according to current scientific evidence.Method: An electronic literature search was carried out until September 2019, with the terms Amelogenesis imperfecta, renal AND/OR Amelogenesis Imperfecta and AND/OR Syndrome Amelogenesis Imperfecta.Results: 1660 articles were pre-selected, of which 52 were taken into account for this review. It was identified that the syndrome Amelogenesis imperfecta-Nephrocalcinosis, Raine syndrome, Bartter syndrome, Distal renal tubular acidosis and familial primary hypomagnesemia with hypercalciuria and nephrocalcinosis are renal conditions that concur concomitantly with a dental phenotype.Conclusion: This review has allowed us to demonstrate that alterations in dental enamel type AI constitute a warning sign for pathological entities that impact renal functioning. It is recommended that dental professionals, an established diagnosis of amelogenesis imperfecta, consider making the referral of these patients to a nephrology service.
Keywords: amelogenesis imperfecta; dental enamel; dental enamel proteins; genes; syndrome